The Properties and a New Preparation of Ethylene Propylene Diene Monomer/Montmorillonite Nanocomposites. Issue 3 (March 2015) - Yang, Ming-Chien; Kao, Bo-Jyue; Tsou, Chi-Hui; Suen, Maw-Cherng; Wu, Chin-San; Tsou, Chih-Yuan; Chu, Chih-Kuei; Yao, Wei-Hua; Wu, Wen-Yan; Hong, Wei-Sung; Lee, Kueir-Rarn
In this study, ethylene propylene diene monomer (EPDM)/organic clay nanocomposites were prepared using melt intercalation to explore how the nanoclay affected their structures and mechanical and thermal properties. Montmorillonite (MMT) modified with hydrochloric acid (HCl) and maleic anhydride (MAH) was employed to improve the compatibility of the EPDM and MMT phases. The effects of the modified clay on the properties of the EPDM were compared with those of commercially available MMTs (Clay10A and Clay30B) synthesized using an alternative modifier. The nanoclay structures of the EPDM/clay nanocomposites were characterized using X-ray diffraction (XRD), and their thermal and mechanical properties were examined a using thermogravimetric analysis (TGA) and universal tensile testing machine. MMT spacing can be increased with the addition of hydrochloric acid and maleic anhydride (MAH). The XRD results showed no diffraction peak for the EPDM and modified MMT (ClayMAH) composites, verifying that the MMT was exfoliated. The TGA results showed that the thermal decomposition temperature and the residual can be enhanced by increasing the ClayMAH content, the pyrolysis temperatures of EPDM/ClayMAH, EPDM/Clay10A, and EPDM/Clay30B are similar because of the barrier effect phenomenon. The mechanical properties can also be improved with additional ClayMAH content because the clay is dispersed in EPDM. A decline in the crosslinking density increases the slidability between polymers, which enhances the mechanical properties of the nanocomposite. ClayMAH is more effective for improving the tensile property compared to Clay10A and Clay30B.